Investigation into porous concrete formation peculiarities with a mixed binder composition - Laukaitis, A. (Journal of Civil Engineering and Management, 1995)
Porous concrete is a cheap material produced from local raw materials. That is why, it is important to improve it's properties, especially the product's density.This paper deals with porous concrete made using a mixed binder composition (lime+Portlandcement) formation peculiarities and determination of optimal product formation parameters for 300–350 kg/m3 product dependency on the binder mixture composition. A wide density interval (200–500 kg/m3) was investigated to determine the optimal above mentioned porous concrete density parameters.It was determined, that the porous concrete density with a mixed binder composition has a complex dependency from water and dry solids ratio (V/K), mixed binder composition and amount of Al powder.Mathematical equations of porous concrete density on technological parameter were derrived. It was found that the lime contant increase in the lime- Portlandcement binder mixture, lowers Al powder effectiveness, increases the product's density and decreases the technological operation time duration.Article in Lithuanian.Dujų betono su mišria rišančiąja medžiaga formavimo ypatumų tyrimaiFirst Published Online: 26 Jul 2012